2015
DOI: 10.1016/j.amepre.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Secular Trends in Obesity Among Chinese Adults, 1991−2011

Abstract: Introduction The prevalence of obesity in Chinese adults increased from 1991 to 2000; however, recent changes in this trend are unclear. This study aims to estimate the current prevalence of obesity and to assess trends in obesity and BMI distribution in Chinese adults from 1991 through 2011. Methods Height and weight measurements of 12,249 Chinese adults from the 2011 China Health and Nutrition Survey were analyzed (in 2013) together with China Health and Nutrition Survey data for 1991–2009. Obesity was def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
96
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(106 citation statements)
references
References 36 publications
10
96
0
Order By: Relevance
“…It has been well documented internationally that higher body weight and lower levels of physical activity are associated with a greater risk of breast cancer incidence and mortality [31], and a Chinese study has also reported an association between body size, fat distribution and breast cancer incidence [32]. As a result of the increasing intake of Western style food and lack of exercise, the proportion of Chinese women who were overweight or obese increased over time from 4.6% in 1991 to 11.0% in 2011 [33]. In general, it is also likely that levels of physical activity amongst Chinese population decreased over time in the cities and more developed areas, while women in rural and less developed areas are still more likely to be undertaking more physical work than those living in more urbanized areas [34].…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented internationally that higher body weight and lower levels of physical activity are associated with a greater risk of breast cancer incidence and mortality [31], and a Chinese study has also reported an association between body size, fat distribution and breast cancer incidence [32]. As a result of the increasing intake of Western style food and lack of exercise, the proportion of Chinese women who were overweight or obese increased over time from 4.6% in 1991 to 11.0% in 2011 [33]. In general, it is also likely that levels of physical activity amongst Chinese population decreased over time in the cities and more developed areas, while women in rural and less developed areas are still more likely to be undertaking more physical work than those living in more urbanized areas [34].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the total fertility rate (average number of children born per women) has dropped tremendously from 6.1 to 1.2 over the past half century; this is mainly attributed to the implementation of a nationwide family planning program in China [8]. Other changes, such as an increasing prevalence of obesity, an earlier age at menarche, a later age at menopause, and an increasing number of lifetime sexual partners, also likely contribute to the burden of gynecological cancers in China [9]. Assessment of trends in cancer incidence and mortality is of the utmost importance to cancer control and public health planning.…”
Section: Introductionmentioning
confidence: 99%
“…According to the 2011 China Health and Nutrition Survey, the age-adjusted overall prevalence of obesity approximately tripled from 3.75% in 1991 to 11.3% in 2011. 8 Previous studies have shown a strong relationship between long-term weight gain and risk of MetS, the person who gained weight since early adulthood was at an increased risk of MetS, as compared to those who maintained a stable weight. But these findings were based on Western or Japanese populations.…”
Section: Introductionmentioning
confidence: 97%